Perkembangan Perkebunan di Aceh Abad Ke XIII – XIX - Dewi Setyawati (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2023)
Aceh has a strategic geographical expanse because it has a port port that was often visited by traders from other nations before the arrival of Islam until the arrival of colonialism. Aceh has relations with other nations because it has several commodities that are in demand by traders from outside the Aceh region. Commodities of the Acehnese people in the pre-Islamic period and the Islamic kingdom (pre-colonial) were the result of plantations. One of the main commodities is Pepper. This study uses historical methods and discourse data analysis. The historical method has several stages, namely heuristics, source criticism, interpretation, and historiography. The purpose of this study was to determine the spice trade, especially pepper, the influence of plantation development on multicultural communities in Aceh from the pre-colonial 13th century to the 19th century. As a trading center, the lives of Acehnese people depended on the results of trade from and inland areas. Goods originating from the interior are transported by boats to the coastal areas and from there they are transported abroad or traded to foreign traders who come there.